Efektivitas Media Pembelajaran Wordwall dalam Meningkatkan Minat Belajar Pendidikan Agama Islam - Setiawan, Yosef; Andrianto, Dedi (Al-Bustan: Jurnal Pendidikan Islam, 2024)
Islamic education at SMPN 02 Abung Pekurun is often perceived as less engaging and fails to receive positive responses from students due to the limited creativity of teachers in utilizing instructional media. A quantitative study was conducted using a Quasi-Experimental approach to evaluate the effect of using the Wordwall website as a learning media in enhancing students' learning interest. The experimental group utilized Wordwall, while the control group employed conventional methods. The t-test results indicate a significant difference in students' learning interest, with the experimental group averaging 59.18 and the control group averaging 47.35. This finding reaffirms that the use of Wordwall can enhance the effectiveness of Islamic education, enrich students' learning experiences, and provide an engaging alternative through technology in the educational process. This research contributes significantly to the development of more innovative and technology-oriented teaching methods.